Perilaku Pemilih Pada Pemilihan Umum Gubernur Sumatera Utara Tahun 2018 di Kecataman Galang - Dita Mandasari; Muhammad Husni Thamrin; Walid Musthafa Sembiring (Universitas Medan Area, 2019)
This research based on a phenomenon the victory of candidate Edy Rahmayadi and Musa Rajekshah in Galang. Galang, where is a town in multi ethnic and religion. Theories used in this study are the theory about the general election, the behavior of voters, and the participation of voters. The population of this research are the citiziens who are domicile in Galang and registered as a voter in 2018 north sumatera governor general election and used 100 sample in this study. The research method used is a quantitative method. The results of research that based on the analysis and evaluation obtained show that religion (the sociological factors), image/figure of a candidate (psychological factors), and the achievements of the candidate (rational factors) have a significant relationship with the behavior of the voters at the general election the Governor of North Sumatra in Galang